Kepemimpinan Transformasional, Motivasi Dan Budaya Organisasi Dampaknya Terhadap Kinerja Perangkat Desa (Survey Pada Perangkat Desa Kecamatan Temon Kabupaten Kulon Progro Propinsi Daerah Istimewa Yogyakarta) - Titi Laras; Raden Tri Haryono (Jurnal Ekonomi, 2016)
This study aims to test and prove empirically transformational leadership, motivation and organizational culture with the device performance of the village in Temon Kulon Progo. The research method used the survey method. The subjects were a village. The total population of this study are 185 respondents, while the total sample of 130 respondents. Method of sampling techniques with non-random sampling with proportional random sampling technique. Data are analyzed using a simple linear regression tool. The results of the research are: (a). There is a positive effect of transformational leadership at the Village performance; (b). There is a positive effect Motivation Performance with the Village and (c) . There is a positive influence on organizational culture with the performance of the village in Temon Kulon Progo.